Efek Work Life Balance terhadap Kinerja Karyawan di Moderasi oleh Keputusan Kerja PT Unirama Duta Niaga - Elga Bayu Santoso; Bambang Suwarsono; Brahma Wahyu Kurniawan (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
The company must be able to make the right policies so that the company can maintain its survival, so that the company can compete with competing companies and gain the trust of consumers. One of the important factors in achieving goals is HR (Human Resources) which has a very important role in determining the success of a company. This research aims to analyze the effect of work-life balance on job satisfaction and employee performance. This type of research uses quantitative research with a questionnaire instrument. The results of descriptive analysis show that all indicators of work-life balance, job satisfaction, and employee performance are in the “Good Enough” category, indicating that respondents' perceptions of work-life balance, job satisfaction, and employee performance still need to be improved. Validity and reliability tests show that the instruments used are valid and reliable. The results of structural model testing show that work-life balance has a significant and strong effect on employee performance (O=0.822; p<0.001) and job satisfaction (O=0.677; p<0.001), while job satisfaction also affects performance (O=0.367; p=0.006). In addition to the direct effect, there is also a significant indirect effect of work-life balance on performance through job satisfaction (O=0.249; p=0.011). Work-life balance improves employee performance, both directly and through increased job satisfaction, so companies are advised to create policies that support work-life balance in order to create a productive and sustainable work environment.